2019
DOI: 10.18632/oncotarget.26775
|View full text |Cite|
|
Sign up to set email alerts
|

Stratifying nonfunctional pituitary adenomas into two groups distinguished by macrophage subtypes

Abstract: Tumor-associated macrophages (TAMs) polarize to M1 and M2 subtypes exerting anti-tumoral and pro-tumoral effects, respectively. To date, little is known about TAMs, their subtypes, and their roles in non-functional pituitary adenomas (NFPAs). We performed flow cytometry on single cell suspensions from 16 NFPAs, revealing that CD11b + myeloid cells comprise an average of 7.3% of cells in NFPAs (range = 0.5%–27.1%), with qPCR revealing most CD11b + cells to be monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…One study that analyzed CD11b-expressing cells (expressed on monocytes, neutrophils, natural killer cells, granulocytes and macrophages) in 16 non-functioning pituitary tumors demonstrated that a higher proportion of CD11 + cells (>10%) was associated with a more expansile and mitotically active tumor. 21 This study also demonstrated that tumors invading the cavernous sinus had a greater presence of immunosuppressive macrophages (M2) than did non-invasive tumors (M2/M1 ratio >1 vs M2/M1 ratio <1). The correlation between increased number of immunosuppressive M2 macrophages and invasive behavior has been described in many cancer types.…”
Section: Discussionsupporting
confidence: 53%
“…One study that analyzed CD11b-expressing cells (expressed on monocytes, neutrophils, natural killer cells, granulocytes and macrophages) in 16 non-functioning pituitary tumors demonstrated that a higher proportion of CD11 + cells (>10%) was associated with a more expansile and mitotically active tumor. 21 This study also demonstrated that tumors invading the cavernous sinus had a greater presence of immunosuppressive macrophages (M2) than did non-invasive tumors (M2/M1 ratio >1 vs M2/M1 ratio <1). The correlation between increased number of immunosuppressive M2 macrophages and invasive behavior has been described in many cancer types.…”
Section: Discussionsupporting
confidence: 53%
“…TAMs can contribute to tumor invasion by promoting tumor cell proliferation, EMT, and invasion as well as suppressing tumoricidal immune cells 8 , 39 , 40 . The important role of TAMs in pituitary tumors has also been highlighted in two other studies 41 , 42 . A variety of cytokines, chemokines, and other immune mediators is secreted by macrophages during immune responses, which serves as a means of intracellular communication 43 .…”
Section: Discussionmentioning
confidence: 58%
“…Higher infiltration of the M2 TAMs is associated with a more aggressive tumor characteristic, reflected by tumor invasion, progression, and metastases. A recent study on non-functional pituitary adenomas (NFPAs) discovered that the cultured M2 macrophages significantly enhanced the proliferation and invasion of the primary NFPA cultures as compared to the cultured M1 macrophages (20). In hepatocellular carcinoma, higher M2 TAMs were strongly correlated with more tumor number and advanced stages (21).…”
Section: M2 Tumor-associated Macrophages-the "Aggressor" Of Tumormentioning
confidence: 99%